MODERASI BERAGAMA SEBAGAI JALAN MENUJU TOLERANSI - Kumowal, Royke Lantupa; Kalintabu, Heliyanti (Peneliti.net, 2024)
Religious moderation teaches the importance of tolerance, dialogue, and mutual understanding among religious communities. In the context of Tumaluntung Village, religious moderation can serve as a solution to address the contestation surrounding the establishment of places of worship. With an inclusive and dialogue-based approach, it is hoped that conflicts and tensions can be minimized. However, implementing religious moderation is not without challenges. One of the greatest challenges is overcoming the distrust and prejudice that have already taken root in the community. Additionally, commitment from all parties, including the government, religious leaders, and the community, is essential to promote religious moderation.This research employs a qualitative method with a retrospective case study approach to examine religious moderation as a pathway to tolerance in the context of contestation over the establishment of places of worship in Tumaluntung Village, North Sulawesi. The objective of this study is to observe the dynamics of religious contestation in the establishment of places of worship in Tumaluntung Village, the factors influencing acceptance or rejection of these establishments, and the role of religious moderation in resolving conflicts that have arisen, thereby facilitating the establishment of places of worship in the village.The findings indicate that the efforts made by the government and the community of Tumaluntung Village have, in effect, practiced the values of religious moderation, which are also supported by the Minahasa philosophy of sitou timou tumou tou, which contains Christian values. In other words, the life of tolerance, mutual respect, and acceptance between different religions, along with a peaceful and harmonious existence that has been cultivated by the government and the community of Tumaluntung, reflects the integration of Christian values, the philosophy of sitou timou tumou tou, and the values of religious moderation.